2016
DOI: 10.1140/epjp/i2016-16233-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and surface enrichment of radionuclides in lead-bismuth eutectic from spallation targets

Abstract: With the development of new high-power neutron spallation sources -both for scientific application and as neutron production tool for accelerator-driven systems-the demand for experimentally obtained nuclear data on the residue nuclei production in the target is constantly increasing. In the present work, we examined two lead-bismuth-eutectic targets, irradiated with high-energy protons, concerning their radionuclide content and the spatial distribution of selected isotopes. The first one was the so-called ISO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, the distribution of nuclides between steel surfaces of components and the LBE itself were studied, and polonium production rates predicted using particle transport codes have been confirmed by radiochemical analysis [8][9][10]. While the MEGAPIE experiment provided valuable qualitative and semi-quantitative information regarding radionuclide transport and retention in an LBE system, further experiments are required to assess the fundamental thermodynamic properties governing retention of radionuclides in the coolant and by surface adsorption effects.…”
mentioning
confidence: 99%
“…For example, the distribution of nuclides between steel surfaces of components and the LBE itself were studied, and polonium production rates predicted using particle transport codes have been confirmed by radiochemical analysis [8][9][10]. While the MEGAPIE experiment provided valuable qualitative and semi-quantitative information regarding radionuclide transport and retention in an LBE system, further experiments are required to assess the fundamental thermodynamic properties governing retention of radionuclides in the coolant and by surface adsorption effects.…”
mentioning
confidence: 99%
“…Unfortunately, solubility information for most of the potential spallation products in LBE or Pb does not exist (121), so their potential impact on corrosion remains unclear. Recently, Hammer-Rotzler et al (132) studied the MEGAPIE and ISOLDE (133) targets and found that lanthanides tend to deposit on free metal surfaces instead of remaining dissolved in the LBE. There is, however, no research specifically studying the impact of lanthanides on the corrosion process.…”
Section: Liquid Metal Environmentsmentioning
confidence: 99%
“…Therefore, they are depleted in the bulk LBE. [23,[25][26][27][28] Surface enrichment was also found for electronegative elements such as chlorine and iodine. [23,29] These findings may be important for the safety assessment of nuclear installations, especially concerning dose rate estimations and the evaluation of structure material damage.…”
Section: Experimental Studiesmentioning
confidence: 99%